Assessment of landslide generated impulse waves in dam reservoirs using empirical relations: a case study on Borçka Dam - Hakan Ersoy; Murat Karahan; Hasan Hüseyin Öztürk (Doğal Afetler ve Çevre Dergisi)
The aim of this study is to investigate environmental effects of impulse waves originated from reactivation of a paleo-landslide located 4 km far from the dam body in Borçka Dam reservoir using empirical relations. Considering different values of landslide width and thickness, 3 different scenarios were defined for the slide of landslide material in volumes ranging from 0.5 to 1 million cubic meters. The wave propagation in the reservoir was defined as radially, and properties of landslide generated impulse waves were evaluated using 3D empirical approaches. For different scenarios, it is determined that the wave height values range between 27.1 and 27.7 m/s, the wave height value for opposite shore reaches 23 m and run-up height value is 42.3 m for highest wave celerity value. The values of wave height and run-up height were calculated as 18.5 m and 32.5 m respectively for lowest wave celerity value. Considering the 4-meter freeboard for the dam, it was determined that the wave propagating through the reservoir and reaching the dam body would not create a danger for the body. Empirical equations can be used for the calculation of landslide-induced wave characteristics for simple reservoir geometries and short distances. But 3D numerical models should be preferred for complex reservoir geometries, and the need to use the landslide volume value to be calculated by applying numerical based slope stability analyzes should not be ignored in these models.